Growth factor for therapeutic angiogenesis in ischemic heart disease: A meta-analysis of randomized controlled trials - Tan, Ling; Long, Lin-Zi; Li, Hong-Zheng; Yang, Wen-Wen; Peng, Yu-Xuan; Lu, Jie-Ming; Liao, Fei-Fei; Ma, Xiao-Chang; Qu, Hua; Fu, Chang-Geng; Zhang, Shan-Shan (Frontiers in Cell and Developmental Biology, 2022)
Aim: This study was designed to systematically evaluate the effects of growth factor (GF) for therapeutic angiogenesis on ischemic heart disease (IHD) by pooling the results of randomized controlled trials (RCTs). Methods and Results: PubMed, EMBASE and CENTRAL databases were searched from inception to October 2022. RCTs, investigating the effects of GF therapy on IHD, were included. The risk bias of included study was assessed according to Cochrane tool. Weighted mean difference (WMD), calculated with fixed effect model or random effect model, was used to evaluate the effects of GF therapy on left ventricular ejection fraction (LVEF) and Canadian Cardiovascular Society (CCS) angina class. Relative risk (RR) was used to evaluate the effects of GF therapy on all-cause mortality, major adverse cardiovascular events (MACE) and revascularization. Meta-analysis, meta-regression analysis and publication bias analysis were performed by RevMan 5.3 or Stata 15.1 software. Twenty-nine studies involving 2899 IHD patients (1577 patients in GF group and 1322 patients in control group) were included. Compared with the control group, GF therapy did not reduce all-cause mortality (RR: 0.82; 95%CI: 0.54-1.24; p = 0.341), MACE ((RR: 0.83; 95%CI: 0.61-1.12; p = 0.227), revascularization (RR: 1.27, 95% CI: 0.82-1.96, p = 0.290) and CCS angina class (WMD: -0.08, 95% CI: −0.36-0.20, p = 0.560). However, GF therapy could increase LVEF during short-term follow-up (<1 year). Conclusion: GF for therapeutic angiogenesis was beneficial for increasing LVEF during short-term follow-up (<1 year), however, the therapy was not efficacious in decreasing all-cause mortality, MACE and revascularization.